The stress response of red sea bream (Pagrus major) at harvest: Toward the development of a humane slaughter method - Joey Arboleda; Athanasios Samaras; Nikos Papandroulakis; Carlos Garcia de Leaniz; Leonidas Papaharisis; Pavlos Pavlidis; Michail Pavlidis (Aquaculture, 2026)

Validation of QTL associated with resistance to Lernanthropus kroyeri in European seabass - Stavroula Oikonomou; Domniki Manousi; Arkadios Dimitroglou; Zoi Kazlari; Dimitrios Loukovitis; Kantham Papanna; Konstantinos Tzokas; Nikos Katribouzas; Leonidas Papaharisis; Costas S. Tsigenopoulos; Dimitrios Chatziplis (Aquaculture, 2025)

A Simple Production Process for Prolonging the Microbiological Shelf-Life and Improving the Sensorial Quality of Refrigerated Shucked Mussel ( Mytilus galloprovincialis ) Products Marketed in Greece - Panayotis D. Karayannakidis; Dimitris Petridis; Sofia Galinou-Mitsoudi; Spyridon A. Tsiaras; Soumela E. Chatziantoniou; Lamprakis Avdelas; Leonidas Papaharisis (Journal of Aquatic Food Product Technology, 2024)

Correlations of betanodavirus load in the brain of experimentally infected sea bass (Dicentrarchus labrax, L.) with varying levels of resistance to viral nervous necrosis - VASILEIOS BAKOPOULOS; ANASTASIA PANAGIOTAKI; MICHAIL-AGGELOS VALSAMIDIS; DANIELLA-MARI WHITE; LEONIDAS PAPAHARISIS; ARKADIOS DIMITROGLOU; ELLI KAKAVA (Mediterranean Marine Science, 2023)
The red-spotted grouper nervous necrosis virus (RGNNV) genotype of Betanodavirus causes significant losses to the European sea bass aquaculture industry. The lack of widely available vaccines against this genotype has led researchers and the industry to investigate other avenues for reducing mortality caused by the disease, such as the selection of resistant stocks. The objectives of this study were: a) to assess the presence of natural resistance in sea bass families propagated in the genetic improvement program of Nireus S.A., Greece and, b) to test an ELISA method able to detect viral coat antigen and measure viral load in the brain of tested fish. The second objective was to investigate virus antigen fluctuations during the course of the infection and its correlation with disease development, mortality and resistance. Further aspects of disease pathogenesis were investigated. A population of sea bass consisting of 89 families was experimentally infected with an RGNNV genotype of Betanodavirus; mortalities were recorded and brain samples from dead and survived fish were collected. Experimental infection of fish resulted in a typical pattern of mortality development that reached 56%. Different levels of natural resistance between families were found with cumulative mortality ranging from 20% to 86.2%. There was no statistical difference between the weight of dead fish and the resistant and susceptible families, except when extreme phenotypes were tested, indicating that the weight of fish that died was not a significant factor of final mortality. Brain virus load in the population as a whole increased sharply until D6 post-infection and then gradually dropped until the end of the experiment. When the viral load in the population (dead and survived fish) was tested against time of death, no correlation was found. In fish that survived the infection, the virus load remained high. The viral load per mg of brain tissue in samples taken from dead fish was not a factor that influenced family cumulative % mortality. Brain samples from survived fish reproduced the disease after infection of healthy fish. This study revealed a natural resistance of sea bass to Betanodavirus infection. This important finding can be used as an additional tool in reducing the mortality of cultured stocks. Additionally, there was clear evidence that fish surviving infection become subclinical carriers of the pathogen. Apparently, survival may not be associated with mechanisms of viral clearance but to other mechanisms that may suspend viral replication or aid infected cell endurance. These findings may assist in developing future vaccines and stock selection. A combination of effective vaccination and resistant stocks could be the way ahead.

Genetic Variability, Population Structure, and Relatedness Analysis of Meagre Stocks as an Informative Basis for New Breeding Schemes - Orestis Nousias; Konstantinos Tzokas; Leonidas Papaharisis; Katerina Ekonomaki; Dimitrios Chatziplis; Costas Batargias; Costas S. Tsigenopoulos (Fishes, 2021)
This study evaluates the genetic diversity of different meagre broodstocks sampled in Greece. A multiplex of twelve microsatellite markers was used to genotype 946 fish from eleven stocks and batches used for broodstock selection, and the genetic data was used to calculate genetic population parameters as well as to investigate the genetic differentiation between stocks. The results from a relatedness analysis were used as the guiding lines for a fine-tuned and overall evaluation of the genetic distance between stocks, and the choice of candidate breeders from some of them. The approach implemented in this study uses well-established population genetics methods to evaluate the selection of breeder candidates in aquaculture commercial conditions utilizing a descriptive genetic data set based on microsatellite analyses, and to outline an efficient methodology for establishing the basis of new breeding schemes.